Preparation method of perovskite cell, perovskite cell and multifunctional layer thereof
By preparing a multifunctional layer on the perovskite layer of perovskite solar cells, using polyhexamethyleneguanidine phosphate to passivate defects and adsorb lead ions, the problems of defects and lead leakage in perovskite batteries are solved, and the performance and environmental safety of the battery are improved.
Patent Information
- Application Number
- CN202510045992.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-15
AI Technical Summary
Perovskite solar cells are prone to body phase and surface defects during the preparation process, resulting in non-radiative recombination and ion migration, reducing component efficiency and life. At the same time, perovskites form lead-containing ions, and leakage may pollute the environment.
A multifunctional layer is prepared on the perovskite layer. The multifunctional layer is formed by annealing solution of polyhexamethyleneguanidine phosphate as the solute and N,N dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, ethanol or isopropanol as solvents. It is used to passivate the shallow defects of the perovskite layer and adsorb free lead ions on the fixed surface.
It improves the photoelectric performance and stability of perovskite solar cells, prevents lead ions leakage and environmental pollution, simplifies the preparation process, and is suitable for perovskite batteries of different components and structures.
Smart Images

Figure CN119836187A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of perovskite solar cells, and in particular to a method for preparing a perovskite cell, a perovskite cell and a multifunctional layer thereof. Background Art
[0002] Perovskite has low preparation cost and excellent photoelectric performance, but a large number of bulk and surface defects will be generated in the preparation process of perovskite film, which will lead to serious non-radiative recombination and ion migration, reducing the efficiency and life of the components; secondly, since perovskite contains lead ions, once the lead ions leak, they will enter the ecological environment, which will not only pollute the environment but also cause serious harm to human life. Therefore, problems such as perovskite surface defects and lead leakage are urgent problems to be solved in the field of perovskite solar cell technology. Summary of the invention
[0003] The present application provides a method for preparing a perovskite cell, a perovskite cell and a multifunctional layer thereof. The perovskite cell comprises a multifunctional layer, and the multifunctional layer contains a polyhexamethylene guanidine phosphate bifunctional surface passivator, which can passivate shallow defects of the perovskite to improve the photoelectric performance and stability of the perovskite solar cell. The phosphate ions have a strong binding force to adsorb and fix free lead ions on the surface of the perovskite to prevent them from leaking and polluting the environment.
[0004] In a first aspect, the present application provides a method for preparing a perovskite battery, wherein the perovskite battery comprises a perovskite layer and a multifunctional layer, and the method comprises: preparing the multifunctional layer on the perovskite layer; wherein the multifunctional layer is formed by annealing a multifunctional layer solution prepared on the perovskite layer; the solute of the multifunctional layer solution comprises polyhexamethyleneguanidine phosphate, the solvent of the multifunctional layer solution comprises one or more of N,N dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, ethanol or isopropanol, and the concentration range of the multifunctional layer solution is 0.5-10mmol / L.
[0005] In some embodiments, the preparing the multifunctional layer on the perovskite layer includes: after the preparation of the perovskite layer, annealing at 70°C for 3 minutes; and, preparing the multifunctional layer solution on the perovskite layer by at least one method selected from spin coating, scraping, spraying, and slit coating, and annealing at 100°C for 30 minutes; or, after the preparation of the perovskite layer, annealing at 100°C for 30 minutes; and, preparing the multifunctional layer solution on the perovskite layer by at least one method selected from spin coating, scraping, spraying, and slit coating, and annealing at 100°C for 10 minutes.
[0006] In some embodiments, the perovskite cell further includes an ITO substrate, an electron transport layer, a hole transport layer, a blocking layer, and an electrode layer; before preparing the multifunctional layer on the perovskite layer, the method further includes: preparing the hole transport layer on the ITO substrate, and preparing the perovskite layer on the hole transport layer; after preparing the multifunctional layer on the perovskite layer, the method further includes: preparing the electron transport layer on the multifunctional layer, preparing the blocking layer on the electron transport layer, and preparing the electrode layer on the blocking layer.
[0007] In some embodiments, the hole transport layer is formed by annealing a hole transport layer solution prepared on the ITO substrate, the solute of the hole transport layer solution is Me-4PACz, the solvent of the hole transport layer solution is isopropanol, and the concentration of the hole transport layer solution is 0.5 mg / ml; the electron transport layer is formed by an electron transport layer solution prepared in the multifunctional layer, the solute of the electron transport layer solution is PCBM, the solvent of the electron transport layer solution is chlorobenzene, and the concentration of the electron transport layer solution is 20 mg / ml; or, the electron transport layer is C 60 Made by evaporation, the vacuum degree of evaporation is less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, the film thickness of the electron transport layer is 15-25nm; the barrier layer is made by BCP evaporation, and the vacuum degree of evaporation is less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, and the film thickness of the barrier layer is 5-10 nm; or SnO2 is prepared as the barrier layer by atomic layer deposition, and the film thickness of the barrier layer is 10-20 nm.
[0008] In some embodiments, the perovskite cell further includes an ITO substrate, an electron transport layer, a hole transport layer, a blocking layer, and an electrode layer; before preparing the multifunctional layer on the perovskite layer, the method further includes: preparing the electron transport layer on the ITO substrate, and preparing the perovskite layer on the electron transport layer; after preparing the multifunctional layer on the perovskite layer, the method further includes: preparing the hole transport layer on the multifunctional layer, preparing the blocking layer on the hole transport layer, and preparing the electrode layer on the blocking layer.
[0009] In some embodiments, the electron transport layer is formed by an electron transport layer solution prepared on the ITO substrate, the solute of the electron transport layer solution is SnO2 colloid, the solvent of the electron transport layer solution is deionized water, and the SnO2 colloid and the deionized water are mixed in a ratio of 1:4; the hole transport layer is formed by a hole transport layer solution prepared in the multifunctional layer, the solute of the hole transport layer solution includes Spiro-OMeTAD, TBP, Li-TFSI, and the solvent of the hole transport layer solution is chlorobenzene; the barrier layer is made of molybdenum oxide evaporation, and the evaporation vacuum is less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, and the film thickness of the barrier layer is 3-15 nm.
[0010] In some embodiments, the perovskite layer is made of a conventional bandgap and a wide bandgap perovskite structure by any one of a dry method, a wet method, a one-step method, and a two-step method, the conventional bandgap has a bandgap range of 1.55 eV, and the wide bandgap has a bandgap range of 1.68 eV; the electrode layer is made by a thermal evaporation method, and the vacuum degree of the evaporation is less than 5*10 -4 Pa, the evaporation rate is 0.2-1.5 angstroms / s, and the evaporation thickness of the electrode layer is 100 nm.
[0011] In a second aspect, the present application provides a multifunctional layer of a perovskite battery, wherein the multifunctional layer is formed by annealing a multifunctional layer solution prepared on the perovskite layer; the solute of the multifunctional layer solution includes polyhexamethyleneguanidine phosphate, and the solvent of the multifunctional layer solution includes one or more of N,N dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, ethanol or isopropanol, and the concentration range of the multifunctional layer solution is 0.5-10mmol / L.
[0012] In some embodiments, the perovskite cell also includes a perovskite layer, and the preparation method of the multifunctional layer is as follows: after the perovskite layer is prepared, annealing at 70°C for 3 minutes; and, preparing the multifunctional layer solution on the perovskite layer by at least one method of spin coating, scraping, spraying, and slit coating, and annealing at 100°C for 30 minutes; or, after the perovskite layer is prepared, annealing at 100°C for 30 minutes; and, preparing the multifunctional layer solution on the perovskite layer by at least one method of spin coating, scraping, spraying, and slit coating, and annealing at 100°C for 10 minutes.
[0013] In a third aspect, an embodiment of the present application provides a perovskite cell, comprising an ITO substrate, a hole transport layer, a perovskite layer, the multifunctional layer described in any one of the second aspects, an electron transport layer, a blocking layer and an electrode layer stacked in sequence; or, comprising an ITO substrate, an electron transport layer, a perovskite layer, the multifunctional layer described in any one of the second aspects, a hole transport layer, a blocking layer and an electrode layer stacked in sequence; the perovskite cell is made by the method described in any one of the first aspects.
[0014] It can be seen that in the embodiments of the present application, a multifunctional layer is prepared on the perovskite layer of the perovskite battery, and the multifunctional layer is formed by annealing the multifunctional layer solution prepared on the perovskite layer; the solute of the multifunctional layer solution includes polyhexamethylene guanidine phosphate, which can passivate shallow defects of the perovskite to improve the photoelectric performance and stability of the perovskite solar cell, and the phosphate ions have a strong binding force with the lead ions, which can adsorb and fix the free lead ions on the surface of the perovskite to prevent them from leaking and polluting the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them,
[0016] Figure 1 The chemical formula of polyhexamethyleneguanidine phosphate provided in the embodiments of the present application;
[0017] Figure 2 A schematic diagram of an inverted perovskite cell structure (pin) is provided for the embodiment of the present application;
[0018] Figure 3 A schematic diagram of a formal perovskite cell structure (nip) is provided for the embodiments of the present application;
[0019] Figure 4 Scanning electron microscope photos of perovskite films prepared by the methods of Comparative Example 1, Example 1 and Example 2 provided in the embodiments of the present application;
[0020] Figure 5 The test results of preparing perovskite cells by the methods of Comparative Example 1, Example 1 and Example 2 provided in the embodiments of the present application are shown in FIG.
[0021] Figure 6 The lead adsorption test results of perovskite batteries prepared by the methods of Comparative Example 1, Example 1 and Example 2 provided in the embodiments of the present application;
[0022] Figure 7Scanning electron microscope photos of perovskite films prepared by the methods of Comparative Example 2, Example 3 and Example 4 provided in the embodiments of the present application;
[0023] Figure 8 The test results of preparing perovskite cells using the methods of Comparative Example 2, Example 3 and Example 4 provided in the embodiments of the present application;
[0024] Fig. 9 JV test results of perovskite cells prepared by the methods of Comparative Example 3, Example 5 and Example 6 provided in the embodiments of the present application;
[0025] Fig.10 The lead adsorption test results of perovskite batteries prepared by the methods of Comparative Example 3, Example 5 and Example 6 provided in the embodiments of the present application;
[0026] Fig.11 JV test results of perovskite cells prepared by the methods of Comparative Example 4, Example 7 and Example 8 provided in the embodiments of the present application;
[0027] Fig.12 The lead adsorption test results of perovskite batteries prepared by the methods of Comparative Example 4, Example 7 and Example 8 provided in the embodiments of the present application. DETAILED DESCRIPTION
[0028] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0029] In a first aspect of the present application, the present application provides a method for preparing a perovskite cell, wherein the perovskite cell comprises a perovskite layer and a multifunctional layer, and the method comprises: preparing the multifunctional layer on the perovskite layer.
[0030] The multifunctional layer is formed by annealing a multifunctional layer solution prepared on the perovskite layer; the solute of the multifunctional layer solution includes polyhexamethylene guanidine phosphate, the solvent of the multifunctional layer solution includes one or more of N,N dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, ethanol or isopropanol, and the concentration range of the multifunctional layer solution is 0.5-10 mmol / L. Polyhexamethylene guanidine phosphate (PHMG-P) (such as Figure 1 The bifunctional surface passivator (chemical formula shown) can passivate shallow defects of perovskite to improve the photoelectric performance and stability of perovskite solar cells. The phosphate ions have strong binding force to adsorb and fix free lead ions on the surface of perovskite to prevent them from leaking and polluting the environment. This method is simple to prepare and easy to operate, and is universal for perovskites of different components and different perovskite battery structures, which is conducive to the industrialization of perovskite batteries.
[0031] In some embodiments, the multifunctional layer is prepared on the perovskite layer, including the following two methods:
[0032] Method 1: After the perovskite layer is prepared, annealing is performed at 70° C. for 3 minutes; and, the multifunctional layer solution is prepared on the perovskite layer by at least one method selected from spin coating, scraping, spraying, and slit coating, and annealing is performed at 100° C. for 30 minutes.
[0033] Method 2: After the perovskite layer is prepared, annealing is performed at 100° C. for 30 minutes; and, the multifunctional layer solution is prepared on the perovskite layer by at least one method selected from spin coating, scraping, spraying, and slit coating, and annealing is performed at 100° C. for 10 minutes.
[0034] In some embodiments, the perovskite cell further includes an ITO substrate, an electron transport layer, a hole transport layer, a blocking layer, and an electrode layer; before preparing the multifunctional layer on the perovskite layer, the method further includes: preparing the hole transport layer on the ITO substrate, and preparing the perovskite layer on the hole transport layer; after preparing the multifunctional layer on the perovskite layer, the method further includes: preparing the electron transport layer on the multifunctional layer, preparing the blocking layer on the electron transport layer, and preparing the electrode layer on the blocking layer.
[0035] See also Figure 2 , Figure 2 A schematic diagram of an inverted perovskite cell structure (pin) is provided for the embodiment of the present application, such as Figure 2 As shown, the inverse perovskite cell structure (pin) 100 includes an ITO substrate 1, a hole transport layer 5, a perovskite layer 3, a multifunctional layer 4, an electron transport layer 2, a blocking layer 6, and an electrode layer 7.
[0036] In some embodiments, the hole transport layer is formed by annealing a hole transport layer solution prepared on the ITO substrate, the solute of the hole transport layer solution is Me-4PACz, the solvent of the hole transport layer solution is isopropanol, and the concentration of the hole transport layer solution is 0.5 mg / ml; the electron transport layer is formed by an electron transport layer solution prepared in the multifunctional layer, the solute of the electron transport layer solution is PCBM, the solvent of the electron transport layer solution is chlorobenzene, and the concentration of the electron transport layer solution is 20 mg / ml; or, the electron transport layer is C 60 Made by evaporation, the vacuum degree of evaporation is less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, the film thickness of the electron transport layer is 15-25nm; the barrier layer is made by BCP evaporation, and the vacuum degree of evaporation is less than 10 -4Pa, the evaporation rate is 0.1-0.5 angstroms / s, and the film thickness of the barrier layer is 5-10 nm; or SnO2 is prepared as the barrier layer by atomic layer deposition, and the film thickness of the barrier layer is 10-20 nm.
[0037] In some embodiments, the perovskite cell further includes an ITO substrate, an electron transport layer, a hole transport layer, a blocking layer, and an electrode layer; before preparing the multifunctional layer on the perovskite layer, the method further includes: preparing the electron transport layer on the ITO substrate, and preparing the perovskite layer on the electron transport layer; after preparing the multifunctional layer on the perovskite layer, the method further includes: preparing the hole transport layer on the multifunctional layer, preparing the blocking layer on the hole transport layer, and preparing the electrode layer on the blocking layer.
[0038] See also Figure 3 , Figure 3 A schematic diagram of a formal perovskite cell structure (nip) is provided for the embodiment of the present application, such as Figure 3 As shown, the formal perovskite cell structure (nip) 200 includes an ITO substrate 1, an electron transport layer 2, a perovskite layer 3, a multifunctional layer 4, a hole transport layer 5, a blocking layer 6, and an electrode layer 7.
[0039] In some embodiments, the electron transport layer is formed by an electron transport layer solution prepared on the ITO substrate, the solute of the electron transport layer solution is SnO2 colloid, the solvent of the electron transport layer solution is deionized water, and the SnO2 colloid and the deionized water are mixed in a ratio of 1:4; the hole transport layer is formed by a hole transport layer solution prepared in the multifunctional layer, the solute of the hole transport layer solution includes Spiro-OMeTAD, TBP, Li-TFSI, and the solvent of the hole transport layer solution is chlorobenzene; the barrier layer is made of molybdenum oxide evaporation, and the evaporation vacuum is less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, and the film thickness of the barrier layer is 3-15 nm.
[0040] In some embodiments, the perovskite layer is made of a conventional bandgap and a wide bandgap perovskite structure by any one of a dry method, a wet method, a one-step method, and a two-step method, the conventional bandgap has a bandgap range of 1.55 eV, and the wide bandgap has a bandgap range of 1.68 eV; the electrode layer is made by a thermal evaporation method, and the vacuum degree of the evaporation is less than 5*10 -4 Pa, the evaporation rate is 0.2-1.5 angstroms / s, and the evaporation thickness of the electrode layer is 100 nm.
[0041] According to each embodiment of the first aspect above, the specific process of preparing the formal perovskite battery structure (NIP) is as follows:
[0042] Step 21, ITO substrate cleaning: Use detergent and tap water to clean impurities and oil stains on the surface of the ITO substrate, then use deionized water, ethanol, and acetone to ultrasonicate for 20 minutes respectively, and finally blow dry with a nitrogen gun.
[0043] Step 22, preparation of electron transport layer: mix SnO2 colloid with deionized water in a ratio of 1:4, shake it evenly before use, and can be prepared by spin coating, scraper coating, spray coating or slit coating.
[0044] Preferably, the present application uses a spin coating method.
[0045] Step 23, preparation of perovskite layer: This application uses conventional band gap (1.55eV) and wide band gap (1.68eV) to prepare perovskite layer, and the perovskite layer can be prepared by any one of dry method, wet method, one-step method and two-step method. The dry method is generally prepared by vacuum deposition, and the wet method mainly includes spin coating, blade coating, spray coating and slit coating. This application mainly uses slit coating and vacuum deposition methods.
[0046] Step 24, preparation of multifunctional layer (passivation layer and lead adsorption layer): the main raw material is polyhexamethylene guanidine phosphate, the solvent is one or more of N, N dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), ethanol or isopropyl alcohol (IPA) as a solvent, the concentration of the multifunctional layer solution is in the range of 0.5-10mmol / L, after the wet film of the perovskite film is prepared, the multifunctional layer solution can be coated on the perovskite film by spin coating, blade coating, spray coating, slit coating, etc., and then annealing is performed. The specific process is as follows:
[0047] A: After the perovskite film is prepared, it is annealed at 70°C for 3 minutes, then the functional layer is prepared, and finally annealed at 100°C for 30 minutes.
[0048] B: After the perovskite film is prepared, it is annealed at 100°C for 30 minutes, then the functional layer is prepared, and finally annealed at 100°C for 10 minutes.
[0049] Step 25, preparation of hole transport layer: 72 mg Spiro-OMeTAD, 28 μL TBP, 18 μL Li-TFSI acetonitrile solution (concentration of 520 mg / mL) were dissolved in 1 ml chlorobenzene, stirred to dissolve, and then prepared by spin coating.
[0050] Step 26, barrier layer preparation: by thermal evaporation method, evaporate the molybdenum oxide material, the evaporation vacuum degree is less than 10- 4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, and the film thickness of the barrier layer is 3-15 nm.
[0051] Step 27, electrode layer preparation: Copper electrodes are prepared by thermal evaporation, and the vacuum degree of evaporation is less than 5*10 -4 Pa, the evaporation rate is 0.2-1.5 angstroms / s, and the evaporation thickness of the electrode layer is 100 nm.
[0052] Among them, the specific process of preparing the inverse perovskite battery structure (pin) is as follows:
[0053] Step 31, ITO substrate cleaning: Use detergent and tap water to clean the impurities and oil stains on the surface of the ITO substrate, then use deionized water, ethanol, and acetone to ultrasonicate for 20 minutes respectively, and finally blow dry with a nitrogen gun.
[0054] Step 32, preparation of hole transport layer: the hole transport material is Me-4PACz, the solvent is isopropanol, the concentration is 0.5 mg / ml, and it can be prepared by one of spin coating, scraper coating, spray coating and slit coating.
[0055] Preferably, the present application uses a spin coating method.
[0056] Step 33, preparation of perovskite layer: The present application uses conventional bandgap (1.55eV) and wide bandgap (1.68eV) perovskite structures to prepare perovskite layers. The perovskite layer can be prepared by any one of dry method, wet method, one-step method and two-step method. The dry method is generally prepared by vacuum deposition, and the wet method mainly includes spin coating, blade coating, spray coating and slit coating. The perovskite layer of the present application is mainly prepared by vacuum deposition and slit coating using the method of enlarging the area.
[0057] Step 34, preparation of multifunctional layer (passivation layer and lead adsorption layer): the main raw material is polyhexamethylene guanidine phosphate, the solvent is one or more of N, N dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), ethanol or isopropyl alcohol (IPA) as a solvent, the concentration of the multifunctional layer solution is in the range of 0.1-10mmol / L, after the wet film of the perovskite film is prepared, the multifunctional layer solution can be coated on the perovskite film by spin coating, blade coating, spray coating, slit coating, etc., and then annealing is performed. The specific process is as follows:
[0058] A: After the perovskite film is prepared, it is annealed at 70°C for 3 minutes, then the functional layer is prepared, and finally annealed at 100°C for 30 minutes.
[0059] B: After the perovskite film is prepared, it is annealed at 100℃ for 30min, then the functional layer is prepared, and finally annealed at 100℃ for 10min.
[0060] The multifunctional layer preparation method can be completed by spin coating, scraper coating, spray coating, slit coating and the like. The present application uses the spin coating method.
[0061] Step 35, preparation of electron transport layer: using 20 mg / ml PCBM solution, the solvent is chlorobenzene, and can be prepared by spin coating, scraper coating, spray coating and slit coating; or thermal evaporation method can be used to prepare C 60 Electron transport layer, the vacuum degree of evaporation is less than 10 -4 Pa, evaporation rate is 0.1-0.5 angstroms / s, C 60 The film thickness is 15-25nm. This application uses evaporation C 60 method.
[0062] Step 36, barrier layer preparation: BCP is deposited by thermal evaporation, and the vacuum degree of the evaporation is less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s and the film thickness is 5-10nm; SnO2 can also be prepared as a barrier layer by atomic deposition (ALD) with a thickness of 10-20nm. This application uses the evaporation BCP method.
[0063] Step 37, electrode layer preparation: copper electrode is prepared by thermal evaporation, and the vacuum degree of evaporation is less than 5*10 -4 Pa, the evaporation rate is 0.2-1.5 angstroms / s, and the evaporation thickness is 100nm.
[0064] In the second aspect of the present invention, the present application provides a multifunctional layer of a perovskite battery, wherein the multifunctional layer is formed by annealing a multifunctional layer solution prepared on the perovskite layer; the solute of the multifunctional layer solution includes polyhexamethyleneguanidine phosphate, and the solvent of the multifunctional layer solution includes one or more of N,N dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, ethanol or isopropanol, and the concentration range of the multifunctional layer solution is 0.5-10mmol / L.
[0065] In some embodiments, the perovskite cell also includes a perovskite layer, and the preparation method of the multifunctional layer is as follows: after the perovskite layer is prepared, annealing at 70°C for 3 minutes; and, preparing the multifunctional layer solution on the perovskite layer by at least one method of spin coating, scraping, spraying, and slit coating, and annealing at 100°C for 30 minutes; or, after the perovskite layer is prepared, annealing at 100°C for 30 minutes; and, preparing the multifunctional layer solution on the perovskite layer by at least one method of spin coating, scraping, spraying, and slit coating, and annealing at 100°C for 10 minutes.
[0066] In the third aspect of the present invention, an embodiment of the present application provides a perovskite cell, comprising an ITO substrate, a hole transport layer, a perovskite layer, the multifunctional layer as described in any one of the second aspects, an electron transport layer, a blocking layer and an electrode layer stacked in sequence; or, comprising an ITO substrate, an electron transport layer, a perovskite layer, the multifunctional layer as described in any one of the second aspects, a hole transport layer, a blocking layer and an electrode layer stacked in sequence; the perovskite cell is made by the method as described in any one of the first aspects.
[0067] The scheme of the present invention is described below by means of specific examples. It should be noted that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention.
[0068] Example 1
[0069] (1) Substrate cleaning: Use detergent and tap water to clean the impurities and oil on the surface of the ITO substrate, then use deionized water, ethanol, and acetone to ultrasonicate for 20 minutes respectively, and finally blow dry with a nitrogen gun.
[0070] (2) Preparation of ITO / Me-4PACz substrate: 0.5 mg Me-4PACz was dissolved in isopropanol and stirred for 2-3 hours to obtain a hole transport layer solution; the cleaned ITO substrate was first placed in a UV-O3 machine for 15 minutes, and then the hole transport layer solution was spin-coated onto the ITO surface. The spin coating process was 3000 rpm for 30 seconds, and the annealing process was 100°C for 10 minutes.
[0071] (3) Preparation of perovskite layer: The perovskite layer uses a 1.55 eV trication perovskite component, Cs 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05)3. The perovskite concentration is 1.1 mol / L. CsI 0.05 mol, FAI 0.9 mmol, MAI 0.05 mmol, PbI2 0.925 mmol, PbBr2 0.075 mmol are dissolved in 0.91 ml of DMF and DMSO mixed solution (DMF:DMSO = 4:1 volume ratio). The size of the perovskite substrate is 5*5 cm 2 , prepared by slit coating, the slit coating gap is 0.1mm, the coating speed is 5mm / s, the solvent extraction is completed by flash evaporation equipment, and the controllable vacuum degree of the flash evaporation equipment is 0.01-10 5 Pa. Place the substrate in (1) on the marble platform of the coating machine, set the above process parameters for coating, and after coating, place the wet film into the flash evaporation equipment for solvent extraction. After flash evaporation for 30 seconds, take out the film and heat it on the set heating table at 100°C for 30 minutes. During the whole process, the ambient humidity is controlled at 20-40%.
[0072] (4) Preparation of multifunctional layer: 3 mg of polyhexamethylene guanidine phosphate was dissolved in 1 ml of IPA, and 15 ul of NMP was added. The solution was stirred thoroughly for 1-2 h to obtain a multifunctional layer solution. The multifunctional layer solution was spin-coated on the surface of the perovskite film in (3) at 5000 rpm for 30 s. After the spin coating, the film was immediately annealed on a 100° C. hot plate for 10 min.
[0073] (5) Preparation of electron transport layer and barrier layer: The film in step (4) is transferred to a vacuum coating machine and evaporated C 60 Electron transport layer and BCP blocking layer. 60 The evaporation process conditions are: evaporation requires a vacuum degree of less than 10 -4 Pa, evaporation rate is 0.1-0.5 angstroms / s, film thickness is 15-30nm; etc. 60 After the evaporation is completed, there is no need to break the cavity and wait for C 60 The source baffle is closed and waits for 5-10 minutes to prevent mutual contamination between sources; then BCP evaporation is started. The evaporation process conditions of BCP are: evaporation requires a vacuum degree of less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, and the film thickness is 5-10 nm.
[0074] (6) Preparation of electrode layer: The film in (5) is transferred to the electrode preparation coating machine. The process conditions for evaporation electrode are: the evaporation requires a vacuum degree of less than 5*10 -4 Pa, the evaporation rate is 0.1-1.5 angstroms / s, and the film thickness is 100 nm.
[0075] The obtained ITO / Me-4PACz / Cs 0.05 (FA 0.95MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3 /
[0076] The PHMG-P / C60 / BCP / Cu structure device was simulated by standard sunlight (100mW / cm 2 The photoelectric conversion efficiency was 21.78% when tested under simulated sunlight (AM1.5).
[0077] Example 2
[0078] (1) ITO cleaning is the same as in Example 1.
[0079] (2) The preparation of ITO / Me-4PACz substrate is the same as that in Example 1.
[0080] (3) Preparation of perovskite layer: The perovskite layer uses a 1.55 eV trication perovskite group, Cs 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3. The perovskite concentration is 1.1 mol / L. CsI 0.05 mol, FAI 0.9 mmol, MAI 0.05 mmol, PbI2 0.925 mmol, PbBr2 0.075 mmol are dissolved in 0.91 ml of DMF and DMSO mixed solution (DMF:DMSO = 4:1 volume ratio). The size of the perovskite substrate is 5*5 cm 2 , prepared by slit coating, the slit coating gap is 0.1mm, the coating speed is 5mm / s, the solvent extraction is completed by flash evaporation equipment, and the controllable vacuum degree of the flash evaporation equipment is 0.01-10 5 Pa. Place the substrate in (1) on the marble platform of the coating machine, set the above process parameters for coating, and after coating, place the wet film into the flash evaporation equipment for solvent extraction. After flash evaporation for 30 seconds, take out the film and heat it on the set heating table at 70°C for 3 minutes. During the whole process, the ambient humidity is controlled at 20-40%.
[0081] (4) Preparation of multifunctional layer: Dissolve 3 mg of polyhexamethylene guanidine phosphate in 1 ml of isopropanol, add 15 ul of NMP, stir thoroughly to dissolve (1-2 h), and spin-coat the solution on the surface of the perovskite film in (3) at 5000 rpm for 30 s. After spin coating, anneal on a 100 °C hot plate for 30 min.
[0082] (5) and (6) are the same as in Example 1.
[0083] The obtained ITO / Me-4PACz / Cs 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3 /
[0084] The PHMG-P / C60 / BCP / Cu structure device was simulated by standard sunlight (100mW / cm 2 The photoelectric conversion efficiency was 23.07% when tested under simulated sunlight (AM1.5).
[0085] Comparative Example 1
[0086] (1) Substrate cleaning: Use detergent and tap water to clean the impurities and oil on the surface of the ITO conductive substrate, then use deionized water, ethanol, and acetone to ultrasonicate for 20 minutes respectively, and finally blow dry with a nitrogen gun.
[0087] (2) Preparation of ITO / Me-4PACz substrate: Dissolve 0.5 mg Me-4PACz in isopropanol and stir for 2-3 hours. First, place the cleaned ITO substrate in a UV-O3 machine for 15 minutes, and then spin-coat the hole transport layer solution onto the ITO surface. The spin coating process is 5000 rpm for 30 seconds, and the annealing process is 100°C for 10 minutes.
[0088] (3) Preparation of perovskite layer: The perovskite layer uses a 1.55 eV trication perovskite group, Cs 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3. The perovskite concentration is 1.1 mol / L. CsI 0.05 mol, FAI 0.9 mmol, MAI 0.05 mmol, PbI2 0.925 mmol, PbBr2 0.075 mmol are dissolved in 0.91 ml of DMF and DMSO mixed solution (DMF:DMSO = 4:1 volume ratio). The size of the perovskite substrate is 5*5 cm 2 , prepared by slit coating, the slit coating gap is 0.1mm, the coating speed is 5mm / s, the solvent extraction is completed by flash evaporation equipment, and the controllable vacuum degree of the flash evaporation equipment is 0.01-10 5Pa. Place the substrate in (1) on the marble platform of the coating machine, set the above process parameters for coating, and after coating, place the wet film into the flash evaporation equipment for solvent extraction. After flash evaporation for 30 seconds, take out the film and heat it on the set heating table at 100°C for 30 minutes. During the whole process, the ambient humidity is controlled at 20-40%.
[0089] (4) Preparation of electron transport layer and barrier layer: The film in (3) was transferred to a vacuum coating machine and evaporated C 60 Electron transport layer and blocking layer. C 60 The evaporation process conditions are: evaporation requires a vacuum degree of less than 10 -4 Pa, evaporation rate is 0.1-0.5 angstroms / s, film thickness is 15-30nm; etc. 60 After the evaporation is completed, there is no need to break the cavity and wait for C 60 The source baffle is closed and waits for 5-10 minutes to prevent mutual contamination between sources; then BCP evaporation is started. The evaporation process conditions of BCP are: evaporation requires a vacuum degree of less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, and the film thickness is 5-10 nm.
[0090] (5) Preparation of electrode layer: The film in (4) is transferred to the coating machine for electrode preparation. The process conditions for evaporation electrode are as follows: the vacuum degree of evaporation is less than 5*10 -4 Pa, the evaporation rate is 0.1-1.5 angstroms / s, and the film thickness is 100 nm.
[0091] The obtained ITO / Me-4PACz / Cs 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3 /
[0092] The PHMG-P / C60 / BCP / Cu structure device was simulated by standard sunlight (100mW / cm 2 The photoelectric conversion efficiency was 18.30% when tested under simulated sunlight (AM1.5).
[0093] In Example 1, Example 2 and Comparative Example 1, the perovskite layer is prepared by a one-step slit coating method, and the perovskite device is a trans structure.
[0094] See Figure 4 , Figure 4From the scanning electron microscope photographs of the perovskite films prepared by the methods of Comparative Example 1, Example 1 and Example 2 provided in the embodiments of the present application, it can be seen that the grains of Example 1 and Example 2 are larger and free of pinholes compared with Comparative Example 1. This is mainly because PHMG-P+NMP can dissolve the perovskite surface and promote the secondary crystallization of the perovskite, thereby improving the crystallization performance of the film; the crystals of Example 2 have further grown relative to Example 1, mainly because in Example 2, the multifunctional layer is prepared after the perovskite is pre-annealed, and the film is not completely crystallized after pre-annealing, and NMP can dissolve more defects on the perovskite surface, while allowing PHMG-P to enter the perovskite crystal, thereby improving the crystallization performance of the film to a greater extent.
[0095] Figure 5 (a) is the JV test result of the perovskite battery prepared by the methods of Comparative Example 1, Example 1 and Example 2 provided in the embodiments of the present application, wherein Voc is the open circuit voltage, PCE (Power conversion efficiency) is the photoelectric conversion efficiency, FF (Fill factor) is the fill factor, Jsc is the short circuit current, and Area is the size of the perovskite battery. It can be seen that the electrical performance of the device has been greatly improved after the preparation of the multifunctional layer; Figure 5 (b) is the stability test result of the perovskite battery prepared by the methods of Comparative Example 1, Example 1 and Example 2 provided in the embodiments of the present application, Figure 5 In (b), the device with PHMG-P passivation maintained its efficiency above 90% of the initial efficiency under LED light source, nitrogen atmosphere, and open circuit condition of 50°C for 1000 hours, while the efficiency of comparative example 1 dropped to below 80% of the initial efficiency after 400 hours.
[0096] Figure 6 The lead adsorption test results of perovskite batteries prepared by the methods of Comparative Example 1, Example 1 and Example 2 provided in the embodiments of the present application are as follows. The prepared devices are immersed in tap water, the lead concentration of the tap water under the initial conditions is tested, and the lead concentration in the water is tested by sampling every 10 minutes (the water is evenly shaken with an oscillator before the test to prevent uneven distribution of lead in the water). It can be seen that in Example 1 and Example 2, the lead concentration in the water has reached the maximum at 20 minutes, and the maximum lead concentration is below the international safety standard of 10 ppm. In contrast, the lead concentration of Comparative Example 1 reaches saturation at 40 minutes, and the lead concentration in the water reaches more than 10 ppm, indicating that PHMG-P can effectively and quickly adsorb lead ions.
[0097] Example 3
[0098] (1) ITO cleaning is the same as in Example 1.
[0099] (2) The preparation of ITO / Me-4PACz substrate is the same as that in Example 1.
[0100] (3) Preparation of perovskite layer: The fully dry method was used to prepare the perovskite layer. Cesium iodide (CsI), formamidine iodide (FAI), ammonium bromide (MABr), lead iodide (PbI2), and lead bromide (PbBr2) were co-evaporated on the substrate of (2) at an evaporation rate ratio of 1:18:0.95:19:1. The temperature of the substrate was set to 50°C. When the vacuum degree reached 10 -4 When the evaporation temperature is below 1000 nm, the evaporation is started and the film thickness is ended when the evaporation thickness reaches 600 nm. The annealing is carried out for 30 minutes on a 150° C. hot stage with the humidity controlled at 30-40%.
[0101] (4) Preparation of multifunctional layer: Dissolve 3 mg of polyhexamethylene guanidine phosphate in 1 ml of isopropanol, add 15 ul of NMP, stir thoroughly to dissolve (1-2 h), and spin-coat the solution on the surface of the perovskite film in (3) at 5000 rpm for 30 s. After spin coating, anneal on a 100 °C hot plate for 10 min.
[0102] (5) and (6) are the same as in Example 1.
[0103] The obtained ITO / Me-4PACz / Cs0.05(FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3 /
[0104] The PHMG-P / C60 / BCP / Cu structured device was tested under standard sunlight simulation (100 mW / cm2 simulated sunlight, AM1.5) and achieved a photoelectric conversion efficiency of 20.31%.
[0105] Example 4
[0106] (1) ITO cleaning is the same as in Example 1.
[0107] (2) The preparation of ITO / Me-4PACz substrate is the same as that in Example 1.
[0108] (3) Preparation of perovskite layer: The fully dry method was used to prepare the perovskite layer. Cesium iodide (CsI), formamidine iodide (FAI), ammonium bromide (MABr), lead iodide (PbI2), and lead bromide (PbBr2) were co-evaporated on the substrate of (2) at an evaporation rate ratio of 1:18:0.95:19:1. The temperature of the substrate was set to 50°C. When the vacuum degree reached 10 -4 When the pressure drops below 0.05 Pa, the evaporation starts and ends when the film thickness reaches 600 nm.
[0109] (4) Preparation of multifunctional layer: Dissolve 3 mg of polyhexamethylene guanidine phosphate in 1 ml of isopropanol, add 15 ul of NMP, stir thoroughly to dissolve (1-2 h), and spin-coat the solution on the surface of the perovskite film in (3) at 5000 rpm for 30 s. After spin coating, anneal on a 150°C hot plate for 30 min.
[0110] (5) and (6) are the same as in Example 1.
[0111] The obtained ITO / Me-4PACz / Cs 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3 /
[0112] PHMG-P / C 60 The device with / BCP / Cu structure was simulated by standard sunlight (100mW / cm 2 The photoelectric conversion efficiency was 21.59% when tested under simulated sunlight (AM1.5).
[0113] Comparative Example 2
[0114] (1) ITO cleaning is the same as in Example 1.
[0115] (2) The preparation of ITO / Me-4PACz substrate is the same as that in Example 1.
[0116] (3) Preparation of perovskite layer: The fully dry method was used to prepare the perovskite layer. Cesium iodide (CsI), formamidine iodide (FAI), ammonium bromide (MABr), lead iodide (PbI2), and lead bromide (PbBr2) were co-evaporated on the substrate of (2) at an evaporation rate ratio of 1:18:0.95:19:1. The temperature of the substrate was set to 50°C. When the vacuum degree reached 10 -4 When the evaporation temperature is below 1000 nm, the evaporation is started and the film thickness is ended when the evaporation thickness reaches 600 nm. The annealing is carried out for 30 minutes on a 150° C. hot stage with the humidity controlled at 30-40%.
[0117] (4) and (5) are the same as (5) and (6) in Example 1.
[0118] The obtained ITO / Me-4PACz / Cs 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3 /
[0119] The PHMG-P / C60 / BCP / Cu structure device was simulated by standard sunlight (100mW / cm 2 The photoelectric conversion efficiency was 16.13% when tested under simulated sunlight (AM1.5).
[0120] In Example 3, Example 4 and Comparative Example 2, the perovskite layer is prepared by a one-step vacuum deposition method, and the device structures thereof are all trans structures. Figure 7 From the scanning electron microscope photos of the perovskite films prepared by the methods of Comparative Example 2, Example 3 and Example 4 provided in the embodiments of the present application, it can be seen that, relative to Comparative Example 2, the perovskite grains of Example 3 and Example 4 are larger and the films are denser, indicating that PHMG-P passivation is also suitable for surface passivation of vacuum deposited films.
[0121] Figure 8 (a) is the JV test result of the perovskite battery prepared by the methods of Comparative Example 2, Example 3 and Example 4 provided in the embodiments of the present application. Compared with Comparative Example 2, the device performance of Example 3 and Example 4 is greatly improved. This is mainly because PHMG-P passivates the perovskite defects and promotes the secondary growth of grains, thereby improving the device performance.
[0122] Figure 8 (b) is the lead adsorption test result of perovskite batteries prepared by the methods of Comparative Example 2, Example 3 and Example 4 provided in the embodiments of the present application. Compared with Comparative Example 2, Example 3 and Example 4 can effectively and quickly adsorb free lead ions to make the lead ion concentration in water lower than 10ppm, indicating that PHMG-P is also suitable for perovskite batteries prepared by vacuum deposition.
[0123] Example 5
[0124] (1) ITO cleaning is the same as in Example 1.
[0125] (2) The preparation of ITO / Me-4PACz substrate is the same as that in Example 1.
[0126] (3) Preparation of perovskite layer: The perovskite layer uses a 1.68 eV wide bandgap component, Cs 0.25 FA 0.75 Pb(I 0.9 Br 0.1 )3. The perovskite concentration is 1.1 mol / L. 0.25 mmol CsI, 0.75 mmol FAI, 0.88 mmol PbI2, 0.12 mmol PbBr2, and 0.2 mmol MACl are dissolved in 0.91 ml of a DMF, DMSO mixed solution (DMF:DMSO = 4:1 volume ratio). The size of the perovskite substrate is 5*5 cm 2, prepared by slit coating, the slit coating gap is 0.1mm, the coating speed is 5mm / s, the solvent extraction is completed by flash evaporation equipment, and the controllable vacuum degree of the flash evaporation equipment is 0.01-10 5 Pa. Place the substrate in (1) on the marble platform of the coating machine, set the above process parameters for coating, and after coating, place the wet film into the flash evaporation equipment for solvent extraction. After flash evaporation for 30 seconds, take out the film and heat it on the set heating table at 120°C for 30 minutes. During the whole process, the ambient humidity is controlled at 20-40%.
[0127] (4) Preparation of multifunctional layer: Dissolve 3 mg of polyhexamethylene guanidine phosphate in 1 ml of isopropanol, add 15 ul of NMP, stir thoroughly to dissolve (1-2 h), and spin-coat the solution on the surface of the perovskite film in (3) at 5000 rpm for 30 s. After spin coating, anneal on a 100 °C hot plate for 10 min.
[0128] (5) and (6) are the same as in Example 1.
[0129] The obtained ITO / Me-4PACz / Cs 0.25 FA 0.75 (PbI 0.9 Br 0.1 )3 / PHMG-P / C60 / BCP / Cu structured devices were simulated under standard sunlight (100mW / cm 2 The photoelectric conversion efficiency was 19.38% when tested under simulated sunlight (AM1.5).
[0130] Example 6
[0131] (1) ITO cleaning is the same as in Example 1.
[0132] (2) The preparation of ITO / Me-4PACz substrate is the same as that in Example 1.
[0133] (3) Preparation of perovskite layer: The perovskite layer uses a 1.68 eV wide bandgap component, Cs 0.25 FA 0.75 Pb(I 0.9 Br 0.1 )3. The perovskite concentration is 1.1 mol / L. 0.25 mmol CsI, 0.75 mmol FAI, 0.88 mmol PbI2, 0.12 mmol PbBr2, and 0.2 mmol MACl are dissolved in 0.91 ml of a DMF, DMSO mixed solution (DMF:DMSO = 4:1 volume ratio). The size of the perovskite substrate is 5*5 cm 2, prepared by slit coating, the slit coating gap is 0.1mm, the coating speed is 5mm / s, the solvent extraction is completed by flash evaporation equipment, and the controllable vacuum degree of the flash evaporation equipment is 0.01-10 5 Pa. Place the substrate in (1) on the marble platform of the coating machine, set the above process parameters for coating, and after coating, place the wet film into the flash evaporation equipment for solvent extraction. After flash evaporation for 30 seconds, take out the film and heat it on the set heating table at 70°C for 3 minutes. During the whole process, the ambient humidity is controlled at 20-40%.
[0134] (4) Preparation of multifunctional layer: Dissolve 3 mg of polyhexamethylene guanidine phosphate in 1 ml of isopropanol, add 15 ul of NMP, stir thoroughly to dissolve (1-2 h), and spin-coat the solution on the surface of the perovskite film in (3) at 5000 rpm for 30 s. After spin coating, anneal on a 120 °C hot plate for 30 min.
[0135] (5) and (6) are the same as in Example 1.
[0136] The obtained ITO / Me-4PACz / Cs 0.25 FA 0.75 (PbI 0.9 Br 0.1 )3 / PHMG-P / C60 / BCP / Cu structured devices were simulated under standard sunlight (100mW / cm 2 The photoelectric conversion efficiency was 21.42% when tested under simulated sunlight (AM1.5).
[0137] Comparative Example 3
[0138] (1) ITO cleaning is the same as in Example 1.
[0139] (2) The preparation of ITO / Me-4PACz substrate is the same as that in Example 1.
[0140] (3) Preparation of perovskite layer: The perovskite layer uses a 1.68 eV wide bandgap component, Cs 0.25 FA 0.75 Pb(I 0.9 Br 0.1 )3. The perovskite concentration is 1.1 mol / L. 0.25 mmol CsI, 0.75 mmol FAI, 0.88 mmol PbI2, 0.12 mmol PbBr2, and 0.2 mmol MACl are dissolved in 0.91 ml of a DMF, DMSO mixed solution (DMF:DMSO = 4:1 volume ratio). The size of the perovskite substrate is 5*5 cm 2, prepared by slit coating, the slit coating gap is 0.1mm, the coating speed is 5mm / s, the solvent extraction is completed by flash evaporation equipment, and the controllable vacuum degree of the flash evaporation equipment is 0.01-10 5 Pa. Place the substrate in (1) on the marble platform of the coating machine, set the above process parameters for coating, and after coating, place the wet film into the flash evaporation equipment for solvent extraction. After flash evaporation for 30 seconds, take out the film and heat it on the set heating table at 70°C for 3 minutes. During the whole process, the ambient humidity is controlled at 20-40%.
[0141] (4) and (5) are the same as (5) and (6) in Example 1.
[0142] The obtained ITO / Me-4PACz / Cs 0.25 FA 0.75 (PbI 0.9 Br 0.1 )3 / PHMG-P / C60 / BCP / Cu structured devices were simulated under standard sunlight (100mW / cm 2 The test was conducted under simulated sunlight (AM1.5), and a photoelectric conversion efficiency of 16.32% was obtained.
[0143] In Example 5, Example 6 and Comparative Example 3, wide bandgap perovskite films were prepared by a one-step slit coating method, respectively, and the device structure thereof was a trans structure.
[0144] Fig. 9 The JV test results of the perovskite cells prepared by the methods of Comparative Example 3, Example 5 and Example 6 provided in the embodiments of the present application show that compared with Comparative Example 3, the electrical performance of the cells in Example 5 and Example 6 is greatly improved, indicating that PHMG-P surface passivation is also suitable for wide-bandgap perovskite films.
[0145] Fig.10 The lead adsorption test results of perovskite batteries prepared by the methods of Comparative Example 3, Example 5 and Example 6 provided in the embodiments of the present application show that, relative to Comparative Example 3, Examples 5 and 6 can quickly absorb free lead ions in the perovskite after passivation with PHMG-P.
[0146] Example 7
[0147] (1) ITO cleaning is the same as in Example 1.
[0148] (2) Preparation of ITO / SnO2 substrate: Mix SnO2 colloid with deionized water in a ratio of 1:4 and shake it evenly before use. First, place the cleaned ITO substrate in a UV-O3 machine for 15 minutes, and then spin-coat the prepared SnO2 transport layer solution onto the ITO surface. The spin-coating process is 3000 rpm for 30 seconds, and the annealing process is 150°C for 20 minutes.
[0149] (3) Preparation of perovskite layer: The perovskite layer uses a 1.55 eV trication perovskite component, Cs 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3. The perovskite concentration is 1.1 mol / L. CsI 0.05 mol, FAI 0.9 mmol, MAI 0.05 mmol, PbI2 0.925 mmol, PbBr2 0.075 mmol are dissolved in 0.91 ml of DMF and DMSO mixed solution (DMF:DMSO = 4:1 volume ratio). The size of the perovskite substrate is 5*5 cm 2 , prepared by slit coating, the slit coating gap is 0.1mm, the coating speed is 5mm / s, the solvent extraction is completed by flash evaporation equipment, and the controllable vacuum degree of the flash evaporation equipment is 0.01-10 5 Pa. Place the substrate in (1) on the marble platform of the coating machine, set the above process parameters for coating, and after coating, place the wet film into the flash evaporation equipment for solvent extraction. After flash evaporation for 30 seconds, take out the film and heat it on the set heating table at 100°C for 30 minutes. During the whole process, the ambient humidity is controlled at 20-40%.
[0150] (4) Preparation of multifunctional layer: Dissolve 3 mg of polyhexamethylene guanidine phosphate in 1 ml of IPA, add 15 ul of NMP, stir thoroughly to dissolve (1-2 h), and spin-coat the solution on the surface of the perovskite film in (3) at 5000 rpm for 30 s. After spin coating, anneal on a 100 °C hot plate for 10 min.
[0151] (5) Preparation of hole transport: 72 mg Spiro-OMeTAD, 28 μL TBP, and 18 μL Li-TFSI acetonitrile solution (concentration of 520 mg / mL) were dissolved in 1 ml chlorobenzene and stirred to dissolve. The completely dissolved solution was spin-coated on the surface of the film in (4) at 5000 rpm for 30 s.
[0152] (6) Preparation of barrier layer: Molybdenum oxide material is evaporated by thermal evaporation, and the vacuum degree of evaporation is less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, and the film thickness is 3-15nm.
[0153] (7) Preparation of electrode layer: Copper electrode is prepared by thermal evaporation method, and the vacuum degree of evaporation is less than 5*10 -4 Pa, the evaporation rate is 0.2-1.5 angstroms / s, and the evaporation thickness is 100nm.
[0154] The obtained ITO / SnO2 / Cs 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3 /
[0155] The PHMG-P / Spiro-OMeTAD / MoO3 / Cu structure device was simulated by standard sunlight (100mW / cm 2 The photoelectric conversion efficiency was 21.49% when tested under simulated sunlight (AM1.5).
[0156] Example 8
[0157] (1) ITO cleaning is the same as in Example 1.
[0158] (2) Preparation of ITO / SnO2 substrate: same as Example 7.
[0159] (3) Preparation of perovskite layer: The perovskite layer uses a 1.55 eV trication perovskite component, Cs 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3. The perovskite concentration is 1.1 mol / L. CsI 0.05 mol, FAI 0.9 mmol, MAI 0.05 mmol, PbI2 0.925 mmol, PbBr2 0.075 mmol are dissolved in 0.91 ml of DMF and DMSO mixed solution (DMF:DMSO = 4:1 volume ratio). The size of the perovskite substrate is 5*5 cm 2 , prepared by slit coating, the slit coating gap is 0.1mm, the coating speed is 5mm / s, the solvent extraction is completed by flash evaporation equipment, and the controllable vacuum degree of the flash evaporation equipment is 0.01-10 5 Pa. Place the substrate in (1) on the marble platform of the coating machine, set the above process parameters for coating, and after coating, place the wet film into the flash evaporation equipment for solvent extraction. After flash evaporation for 30 seconds, take out the film and heat it on the set heating table at 70°C for 3 minutes. During the whole process, the ambient humidity is controlled at 20-40%.
[0160] (4) Preparation of multifunctional layer: Dissolve 3 mg of polyhexamethylene guanidine phosphate in 1 ml of IPA, add 15 ul of NMP, stir thoroughly to dissolve (1-2 h), and spin-coat the solution on the surface of the perovskite film in (3) at 5000 rpm for 30 s. After spin coating, anneal on a hot plate at 100 °C for 30 min.
[0161] (5) Hole transport preparation: same as step (5) in Example 7.
[0162] (6) Preparation of barrier layer: Molybdenum oxide material is evaporated by thermal evaporation, and the vacuum degree of evaporation is less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, and the film thickness is 3-15nm.
[0163] (7) Preparation of electrode layer: Copper electrode is prepared by thermal evaporation method, and the vacuum degree of evaporation is less than 5*10 -4 Pa, the evaporation rate is 0.2-1.5 angstroms / s, and the evaporation thickness is 100nm.
[0164] The obtained ITO / SnO2 / Cs 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3 /
[0165] The PHMG-P / Spiro-OMeTAD / MoO3 / Cu structure device was simulated by standard sunlight (100mW / cm 2 The photoelectric conversion efficiency was 22.71% when tested under simulated sunlight (AM1.5).
[0166] Comparative Example 4
[0167] (1) ITO cleaning is the same as in Example 1.
[0168] (2) Preparation of ITO / SnO2 substrate: Mix SnO2 colloid with deionized water in a ratio of 1:4 and shake it evenly before use. First, place the cleaned ITO substrate in a UV-O3 machine for 15 minutes, and then spin-coat the prepared SnO2 transport layer solution onto the ITO surface. The spin-coating process is 3000 rpm for 30 seconds, and the annealing process is 150°C for 20 minutes.
[0169] (3) Preparation of perovskite layer: The perovskite layer uses a 1.55 eV trication perovskite component, Cs 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I0.95 Br 0.05 )3. The perovskite concentration is 1.1 mol / L. CsI 0.05 mol, FAI 0.9 mmol, MAI 0.05 mmol, PbI2 0.925 mmol, PbBr2 0.075 mmol are dissolved in 0.91 ml of DMF and DMSO mixed solution (DMF:DMSO = 4:1 volume ratio). The size of the perovskite substrate is 5*5 cm 2 , prepared by slit coating, the slit coating gap is 0.1mm, the coating speed is 5mm / s, the solvent extraction is completed by flash evaporation equipment, and the controllable vacuum degree of the flash evaporation equipment is 0.01-10 5 Pa. Place the substrate in (1) on the marble platform of the coating machine, set the above process parameters for coating, and after coating, place the wet film into the flash evaporation equipment for solvent extraction. After flash evaporation for 30 seconds, take out the film and heat it on the set heating table at 100°C for 30 minutes. During the whole process, the ambient humidity is controlled at 20-40%.
[0170] (4) Hole transport preparation: same as step (5) in Example 7.
[0171] (5) Preparation of barrier layer: Molybdenum oxide material is evaporated by thermal evaporation, and the vacuum degree of evaporation is less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, and the film thickness is 3-15nm.
[0172] (6) Preparation of electrode layer: Copper electrode is prepared by thermal evaporation method, and the vacuum degree of evaporation is less than 5*10 -4 Pa, the evaporation rate is 0.2-1.5 angstroms / s, and the evaporation thickness is 100nm.
[0173] The obtained ITO / SnO2 / Cs 0.05 (FA 0.95 MA 0.05 ) 0.95 Pb(I 0.95 Br 0.05 )3 /
[0174] The PHMG-P / Spiro-OMeTAD / MoO3 / Cu structure device was simulated by standard sunlight (100mW / cm 2 The photoelectric conversion efficiency was 17.33% under simulated sunlight (AM1.5).
[0175] Example 7, Example 8 and Comparative Example 4 respectively prepared gap perovskite films by a one-step slit coating method, and their device structures were formal structures.
[0176] Fig.11The JV test results of the perovskite cells prepared by the methods of Comparative Example 4, Example 7 and Example 8 provided in the embodiments of the present application show that compared with Comparative Example 4, the electrical performance of the devices in Example 7 and Example 8 are greatly improved, indicating that PHMG-P can effectively passivate the defects of formal perovskite cells.
[0177] Fig.12 The lead adsorption test results of perovskite batteries prepared by the methods of Comparative Example 4, Example 7 and Example 8 provided in the embodiments of the present application show that compared with Comparative Example 4, Example 7 and Example 8 can quickly and effectively adsorb lead ions, indicating that PHMG-P is also applicable to formal structures.
[0178] As can be seen from the above embodiments, the present application prepares a multifunctional layer on the perovskite layer of the perovskite cell, and the multifunctional layer is formed by annealing the multifunctional layer solution prepared on the perovskite layer; the solute of the multifunctional layer solution includes polyhexamethylene guanidine phosphate, which can passivate the shallow defects of the perovskite to improve the photoelectric performance and stability of the perovskite solar cell, and the phosphate ions have a strong binding force to adsorb and fix the free lead ions on the surface of the perovskite, preventing them from leaking and polluting the environment. This method is simple to prepare and easy to operate, and is universal for perovskites of different components and different perovskite cell structures, which is conducive to the industrialization of perovskite cells.
[0179] Unless otherwise specified, all terms used in the present invention have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. All patents and publications related to the present invention are incorporated herein by reference in their entirety. The term "comprising" or "including" is an open expression, that is, including the contents specified in the present invention, but does not exclude contents in other aspects.
[0180] In the description of this specification, the description with reference to the terms "one embodiment", "another embodiment", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory. In addition, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated.
[0181] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a perovskite battery, characterized in that: The perovskite cell comprises a perovskite layer and a multifunctional layer, and the method comprises: preparing the multifunctional layer on the perovskite layer; The multifunctional layer is formed by annealing a multifunctional layer solution prepared on the perovskite layer; the solute of the multifunctional layer solution includes polyhexamethyleneguanidine phosphate, the solvent of the multifunctional layer solution includes one or more of N,N dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, ethanol or isopropanol, and the concentration range of the multifunctional layer solution is 0.5-10mmol / L.
2. The method according to claim 1, characterized in that The step of preparing the multifunctional layer on the perovskite layer comprises: After the perovskite layer is prepared, annealing is performed at 70° C. for 3 min; and, the multifunctional layer solution is prepared on the perovskite layer by at least one method selected from spin coating, blade coating, spray coating, and slit coating, and annealing is performed at 100° C. for 30 min; or, After the perovskite layer is prepared, annealing is performed at 100° C. for 30 minutes; and the multifunctional layer solution is prepared on the perovskite layer by at least one method selected from spin coating, blade coating, spray coating, and slit coating, and annealing is performed at 100° C. for 10 minutes.
3. The method according to claim 1 or 2, characterized in that: The perovskite cell also includes an ITO substrate, an electron transport layer, a hole transport layer, a barrier layer, and an electrode layer; Before preparing the multifunctional layer on the perovskite layer, the method further comprises: preparing the hole transport layer on the ITO substrate, and preparing the perovskite layer on the hole transport layer; After preparing the multifunctional layer on the perovskite layer, the method further comprises: preparing the electron transport layer on the multifunctional layer, preparing the barrier layer on the electron transport layer, and preparing the electrode layer on the barrier layer.
4. The method according to claim 3, characterized in that The hole transport layer is formed by spin coating a hole transport layer solution on the ITO substrate and then annealing the solution, the solute of the hole transport layer solution is Me-4PACz, the solvent of the hole transport layer solution is isopropanol, and the concentration of the hole transport layer solution is 0.5 mg / ml; The electron transport layer is formed by the electron transport layer solution prepared in the multifunctional layer, the solute of the electron transport layer solution is PCBM, the solvent of the electron transport layer solution is chlorobenzene, and the concentration of the electron transport layer solution is 20 mg / ml; or the electron transport layer is C 60 Made by evaporation, the vacuum degree of evaporation is less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, and the film thickness of the electron transport layer is 15-25 nm; The barrier layer is made by BCP evaporation, and the vacuum degree of evaporation is less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, and the film thickness of the barrier layer is 5-10 nm; or SnO2 is prepared as the barrier layer by atomic layer deposition, and the film thickness of the barrier layer is 10-20 nm.
5. The method according to claim 1 or 2, characterized in that: The perovskite cell also includes an ITO substrate, an electron transport layer, a hole transport layer, a barrier layer, and an electrode layer; Before preparing the multifunctional layer on the perovskite layer, the method further comprises: preparing the electron transport layer on the ITO substrate, and preparing the perovskite layer on the electron transport layer; After preparing the multifunctional layer on the perovskite layer, the method further comprises: preparing the hole transport layer on the multifunctional layer, preparing the blocking layer on the hole transport layer, and preparing the electrode layer on the blocking layer.
6. The method according to claim 5, characterized in that The electron transport layer is formed by an electron transport layer solution prepared on the ITO substrate, the solute of the electron transport layer solution is SnO2 colloid, the solvent of the electron transport layer solution is deionized water, and the SnO2 colloid and the deionized water are mixed in a ratio of 1:4; The hole transport layer is formed by a hole transport layer solution prepared in the multifunctional layer, the solute of the hole transport layer solution includes Spiro-OMeTAD, TBP, and Li-TFSI, and the solvent of the hole transport layer solution is chlorobenzene; The barrier layer is made by evaporation of molybdenum oxide, and the evaporation vacuum is less than 10 -4 Pa, the evaporation rate is 0.1-0.5 angstroms / s, and the film thickness of the barrier layer is 3-15 nm.
7. The method according to any one of claims 1 to 6, characterized in that: The perovskite layer is made of a conventional bandgap and a wide bandgap perovskite structure by any one of a dry method, a wet method, a one-step method, and a two-step method, the conventional bandgap has a bandgap range of 1.55 eV, and the wide bandgap has a bandgap range of 1.68 eV; The electrode layer is made by thermal evaporation, and the vacuum degree of evaporation is less than 5*10 -4 Pa, the evaporation rate is 0.2-1.5 angstroms / s, and the evaporation thickness of the electrode layer is 100 nm.
8. A multifunctional layer of a perovskite battery, characterized in that: The multifunctional layer is formed by annealing a multifunctional layer solution prepared on the perovskite layer; The solute of the multifunctional layer solution includes polyhexamethyleneguanidine phosphate, the solvent of the multifunctional layer solution includes one or more of N,N dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, ethanol or isopropanol, and the concentration range of the multifunctional layer solution is 0.5-10mmol / L.
9. The multifunctional layer according to claim 8, characterized in that The perovskite cell further includes a perovskite layer, and the preparation method of the multifunctional layer is as follows: After the perovskite layer is prepared, annealing is performed at 70° C. for 3 min; and, the multifunctional layer solution is prepared on the perovskite layer by at least one method selected from spin coating, blade coating, spray coating, and slit coating, and annealing is performed at 100° C. for 30 min; or, After the perovskite layer is prepared, annealing is performed at 100° C. for 30 minutes; and the multifunctional layer solution is prepared on the perovskite layer by at least one method selected from spin coating, blade coating, spray coating, and slit coating, and annealing is performed at 100° C. for 10 minutes.
10. A perovskite battery, characterized in that: It comprises an ITO substrate, a hole transport layer, a perovskite layer, the multifunctional layer according to any one of claims 8 to 9, an electron transport layer, a barrier layer and an electrode layer which are stacked in sequence; or it comprises an ITO substrate, an electron transport layer, a perovskite layer, the multifunctional layer according to any one of claims 8 to 9, a hole transport layer, a barrier layer and an electrode layer which are stacked in sequence; The perovskite cell is manufactured by the method according to any one of claims 1 to 7.